Resilience and growth in the small states of the Pacific - Khor, Hoe Ee; Kronenberg, Roger P.; Tumbarello, Patrizia (Washington, D.C International Monetary Fund (IMF), 2016)
Pacific island countries face unique challenges to realizing their growth potential and raising living standards. This book discusses ongoing challenges facing Pacific island countries and policy options to address them. Regional cooperation and solutions tailored to their unique challenges, as well as further integration with the Asia and Pacific region will each play a role. With concerted efforts, Pacific island countries can boost potential growth, increase resilience, and improve the welfare of their citizens.​
Part I. Setting the statge: the quest for resilience and growth in the Pacific Islands -- 1. Economic growth int he Pacific Island countries: challenges, constraints, and policy responses / Roger P. Kronenberg, Hoe Ee Khor -- 2. Raising potential growth and enhancing resilience to shocks / Ezequiel Cabezon, Patrizia Tumbarello, Yiqun Wu -- 3. Building resilience in the Pacific Island countries / Lino Briguglio -- 4. The Pacific speed of growth: how fast can it be and what determines it? / Yongzheng Yang, Hong Chen, Shiu Raj Singh, Baljeet Singh -- 5. Strengthening macro-fiscal resilience to natural disasters and climate change in the small states of the Pacific / Ezequiel Cabezon, Leni Hunter, Patrizia Tumbarello, Kazuaki Washimi, Yigun Wu -- Part II. Managing external spillovers, shocks, and vulnerabilities -- 6. Global and regional spillovers to Pacific Island countries / Fazurin Jamaludin, Niamh Sheridan, Patrizia Tumbarello, Yiqun Wu, TIek Zeinullayev -- 7. Major economic shocks and Pacific Island countries during the global economic crisis / Patrick Colmer, Richard Wood -- 8. Drivers of inflation in hte Pacific Island countries / Zuefei Bai, Patrizia Tumbarello, Yiqun Wu -- 9. Vulnerabilities of isolated small island states in the Pacific -- Part III. Tailoring macroeconomic policies to the small states of the Pacific -- 10. Strengthening fiscal frameworks and improving the spending mix in small states / Ezequiel Cabeson, Patrizia Tumbarello, Yiqun Wu -- 11. Estimating fiscal multipliers using a simplified general equilibrium model of small states, with application to Kiribati and Palau / Sergei Dodzin, Xuefei Bai -- 12. Monetary policy transmission mechanisms in Pacific Island countries / Yongzheng Yang, Matt Davies, Shengzu Wang, Jonathan Dunn, Yiqun Wu -- 13. Global commodity prices, monetary transmission and exhange rate pass-through / Shanaka J. Peiris, Ding Ding -- 14. The role of excess liquidity and interest rate pass-through for the monetary transmission mechanism in the Pacific / Jan Gottschalk -- Part IV. Removing structural impediments to growth -- 15. Planning public financial management reforms in Pacific Island countries / Tobias Haque, Richard Bontjer, Mary Betley, Ron Hackett -- 16. Pacific Island countries: trade integration in a changing global economy / Hong Chen, Lanieta Rauqeuqe, Shiu Raj Sing, Yiqun Wu, Yongzheng Yang -- 17. Determinants of interest rate spreads in the Solomon Islands . Nooman Rebei -- 18. Interest rates, bank profitability, and capital adequacy in the South Pacific / Matt Davies, John Vaught, Ezequiel Cabezon --
Includes Bibliographical refernces and index
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; PACIFIC ISLANDS